1992
DOI: 10.1091/mbc.3.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of HeLa cells on a collagen substratum requires a second messenger formed by the lipoxygenase metabolism of arachidonic acid released by collagen receptor clustering.

Abstract: HeLa cells attach to a variety of substrata but spread only on collagen or gelatin. Spreading is dependent on collagen-receptor upregulation, clustering, and binding to the cytoskeleton. This study examines whether second messengers are involved in initiating the spreading process on gelatin. The levels of cytosolic free calcium ([Ca++]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 43 publications
9
56
0
Order By: Relevance
“…This is supported by the observations that addition of exogenous LTB4 to NIH-3T3 fibroblasts increased the rate and extent of cell spreading ( Figures 3A and 4C), while addition of exogenous PGE2 increased the rate of migration (Figure 8). These data support that spreading and migration rates are limited by the mass of AA oxidized, respectively, by LOX and COX, and are an extension of previous work showing that the overall rate of adhesion is limited by the mass of AA produced by the cells (Chun and Jacobson, 1992). In essence, the regulation of spreading and migration by AA conforms to the law of mass action as elucidated by Waage and Guldberg in 1879 (Janin, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is supported by the observations that addition of exogenous LTB4 to NIH-3T3 fibroblasts increased the rate and extent of cell spreading ( Figures 3A and 4C), while addition of exogenous PGE2 increased the rate of migration (Figure 8). These data support that spreading and migration rates are limited by the mass of AA oxidized, respectively, by LOX and COX, and are an extension of previous work showing that the overall rate of adhesion is limited by the mass of AA produced by the cells (Chun and Jacobson, 1992). In essence, the regulation of spreading and migration by AA conforms to the law of mass action as elucidated by Waage and Guldberg in 1879 (Janin, 1996).…”
Section: Discussionsupporting
confidence: 88%
“…The observation that all general inhibitors of all PLA2s inhibited spreading (mepacrine and BPB), the more selective inhibitor of both iPLA2 and cPLA2 also inhibited spreading (AACOCF3), but the specific inhibitor of iPLA2 did not (HELSS), supports the idea that cPLA2 is the predominant isoform of PLA2 signaling cell spreading in fibroblasts, as was previously shown with HeLa cells (Crawford and Jacobson, 1998). The above-mentioned results are also consistent with previous work demonstrating that the amount of AA produced by cells during adhesion is ratelimiting with respect to the rate and extent of cell spreading (Chun and Jacobson, 1992;Crawford and Jacobson, 1998). …”
supporting
confidence: 92%
See 1 more Smart Citation
“…These complex interactions are initiated in part by receptor-mediated events involving integrin (Hynes, 1992) as well as non-integrin cell surface molecules (Lu et al, 1992). Previous studies have shown that integrin clustering during HeLa cell attachment to a gelatin substrate induces a release of AA (Chun and Jacobson, 1992). AA release is essential for cell spreading on a collagen or gelatin substrate, because inhibition of PLA 2 -dependent spreading can be overcome by the addition of exogenous AA (Chun and Jacobson, 1992;Auer and Jacobson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Each stage of cell adhesion involves changes in overall morphology and cytoskeletal structure that are regulated inter alia by the oxidative enzymes of the AA cascade: LOX and COX. LOX and COX compete for AA released from membranes by phospholipase A 2 (PLA 2 ) to convert it to either leukotriene (LT) or prostaglandin (PG), respectively (1,6,33). More specifically, the conversion of AA to LTB 4 via 5-LOX initiates a cascade of second messengers leading to actin polymerization and thereby activating cell spreading (4) (Stockton RA, Katsumi A, Dixon DA, Green JA, Roberts LA, and Jacobson BS, unpublished observations).…”
mentioning
confidence: 99%